Coupling effect of pressure and flow fields on the crystallization of Poly(vinylidene fluoride)/Poly(methyl methacrylate) miscible blends. (2nd April 2021) - Ren, Jia-Yi; Yang, Shu-Gui; Li, Yue; Lei, Jun; Huang, Hua-Dong; Pan, Mingwang; Lin, Hao; Zhong, Gan-Ji; Li, Zhong-Ming
Abstract: During polymer processing, the polymeric blends are inevitably subjected to coupled external fields (flow, pressure, and temperature), which have great effects on the phase behavior, crystallization behavior, crystalline structure, and final properties of blends. A typical crystalline/amorphous miscible blend system, poly(vinylidene fluoride)/Poly(methyl methacrylate) (PVDF/PMMA) blend, is chosen to understand the coupling effect of processing fields on crystallization behavior of the blends. It is found that shear flow can induce locally oriented trans conformation, which finally transforms into polar β/γ phases during isothermal crystallization under pressure. Interestingly, under pressure, β and γ phases exhibit different sensitivities to shear rate. The γ phase is easily formed at low shear rate, while higher shear rate is required to induce β phase formation, which could be related to the sequence length of the oriented trans conformation induced by shear flow. As for the addition of PMMA, the hydrogen bonding interactions between carbonyl groups of PMMA and hydrogen atom of PVDF could stabilize the shear-induced local trans conformation and subsequently lead to more β/γ phases. Meanwhile, different from PVDF crystallized under static condition, the shear flow and PMMA synergistically induce the transformation from spherulitic to shish-kebab-like structure and highly oriented thick β phase with higher melting point. To the best of our knowledge, it is the first time to reveal the unique crystallization behaviors of PVDF/PMMA blends induced by flow field coupled with pressure. This work could provide a significant guidance for the control of crystal polymorphs of PVDF/PMMA miscible blends during processing. Graphical abstract: Image 1 Highlights: The coupling effect of pressure and shear fields on the crystallization behavior of PVDF/PMMA blends were studied. β/γ phases show different sensitivities to shear rate under pressure, depending on the length of trans-sequences induced. Adding PMMA (10 wt%) stabilizes the shear-induced local trans conformation, resulting in more β/γ phases than neat PVDF. Shear flow and PMMA synergistically induce shish-kebab-like structure and highly oriented thick β phase under pressure.